Parents' Perspective of Antibiotic Usage in Children: A Nationwide Survey in Italy. Issue 10 (15th June 2021) - Pierantoni, Luca; Lo Vecchio, Andrea; Lenzi, Jacopo; Corsi, Vincenza; Campana, Lara; Luca Trobia, Gian; Amendolea, Antonella; Di Felice, Benedetta; Alighieri, Giovanni; Fabrizio, Giovanna Carmela; Bisceglia, Massimo; Peia, Francesco; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Antibiotics represent the most widely prescribed drugs in children worldwide, both in hospital and community settings. A comprehensive approach to understanding the reasons and determinants of antibiotic prescription in the pediatric age is needed. This study aimed to assess parents' attitudes and perspectives about antibiotic use. Methods: Prospective observational study was conducted in all Italian Regions between February 1 and April 30, 2020, using a standardized questionnaire. Results: Six thousand six hundred twenty-five parents from all Italian regions completed the survey. Seventy-six percent of parents were aware that only bacteria are the target of antibiotics, but 92.9% knew that the antibiotic has no direct effect on fever. Antibiotic self-prescription (10.4%) or by remote consultation by phone call (19.9%) or message (9.6%) were relatively common. Ninety-three percent of parents were aware that excessive use of antibiotics could select resistant bacteria and 84.7% of them knew that they could actively fight antibiotic resistance. About two thirds of participants (66.1%) received information on antibiotic resistance from their family pediatrician. Parents born of Italy or those with lower income had a higher probability of having less information from pediatricians or knowledge of proper antibiotic use. Discussion: Our study suggests that parents' knowledge and attitudes toward antibiotic use and prescription are improving compared with previous studies, while there is still a gap regarding antibiotic resistance, particularly on practices that can reduce its burden. Our study's negative finding is that families from low-income settings or those born abroad have significantly more misconceptions about important antibiotic practices.